Electrical properties of multiwalled carbon nanotubes /polyaniline nanocomposite - Das S.K.; Prakash R. (My University, 2025)
A nanocomposite of functionalized 2.5 wt.% carboxylated multiwalled carbon nanotubes (MWCNTs) / polyaniline (PANi) is synthesized using in situ chemical polymerization method. MWCNT is coated by using in-situ chemical polymerization of Polyaniline polymer. Structure and morphology of nanocomposite is characterized, using X-ray diffraction pattern (XRD),scanning electron microscopy (SEM) and transmission electron microscopy (TEM), demonstrate that a thin layer of PANi (polyaniline) is well coated on the surface of MWCNT. Electrical properties were characterized using four probe conductivity measurement and electrochemical impedance spectroscopy. The conductivity of PANI-coated MWCNT increases by a factor of three orders due to the incorporation of PANi onto the pore surface of MWNT. The double layer capacitance is also calculated using impedance measurement.